2021
DOI: 10.1088/1742-6596/2051/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Investigation on Different Bone Densities to avoid Thermal Necrosis during Bone Drilling Process

Abstract: Bone drilling is a universal surgical procedure commonly used for internal fracture fixation, implant placement, or reconstructive surgery in orthopedics and dentistry. The increased temperature during such treatment increases the risk of thermal penetration of the bone, which may delay healing or compromise the fixation’s integrity. Thus, avoiding penetration during bone drilling is critical to ensuring the implant’s stability, which needs surgical drills with an optimized design. Bovine femur and mandible bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The main section of interest in the femur bones was the middle diaphysis, which contains the most compact bone compared to other regions of the skeletal system. This compact bone, commonly known as cortical bone, coexists with a less dense and more porous section called trabecular bone [4]. To this study, the researchers specifically focused on the cortical bone obtained from the femoral shaft of young cows aged between two and three years [5].…”
Section: Bone Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main section of interest in the femur bones was the middle diaphysis, which contains the most compact bone compared to other regions of the skeletal system. This compact bone, commonly known as cortical bone, coexists with a less dense and more porous section called trabecular bone [4]. To this study, the researchers specifically focused on the cortical bone obtained from the femoral shaft of young cows aged between two and three years [5].…”
Section: Bone Specimen Preparationmentioning
confidence: 99%
“…Numerous research studies have explored the effects of drilling conditions, bone type, density, drill-bit shape, and irrigation on maximum temperatures and exposure periods during bone drilling, with the aim of identifying factors to prevent thermal osteonecrosis [3][4][5]. However, some studies have reported contradictory results, which might be attributed to sources of measurement uncertainty rather than the analytical methodologies employed [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Conical drill bits have been shown to lead to substantial heat elevation because of the increased friction caused by their wider cutting surface at the base [6]. Similar to the effect of twist bits, the heat generated by conical bits can risk causing thermal osteonecrosis, posing IOP Publishing doi:10.1088/1742-6596/2643/1/012020 2 a threat to the success of surgical procedures [7]. Understanding these thermal effects is critical for improving surgical techniques and preventing bone damage during orthopedic operations [8].…”
Section: Introductionmentioning
confidence: 99%